2004
DOI: 10.1002/ajhb.20083
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, aging, and body composition in men from Harare, Zimbabwe

Abstract: To examine age-related changes in body composition and testosterone (T) among men in an urban sub-Saharan African population, measures of body composition and salivary T were obtained from 109 males ages 20-78 in Harare, Zimbabwe. Measures included height, weight, suprailiac and triceps skinfold, and percent body fat by bioelectric impedance (BIA). Saliva samples were assayed for T using radioimmunoassay. Average BMI of the overall sample (23.16 (SD = 18.12) kg/m(2) was close to Western populations, while sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
19
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
3
19
1
Order By: Relevance
“…Gray and colleagues reported a downward trend, although not prominent, in salivary testosterone levels with age for Kenyan Ariaal men who have a subsistence livelihood. 10 Similar findings have also been reported in Zimbabwean men 11 , American men, 7,8,12 and Japanese men. 13 Testosterone levels can differ among different ethnic groups; Pakistani men have lower testosterone levels than men from Europe, Africa, and the Caribbean.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Gray and colleagues reported a downward trend, although not prominent, in salivary testosterone levels with age for Kenyan Ariaal men who have a subsistence livelihood. 10 Similar findings have also been reported in Zimbabwean men 11 , American men, 7,8,12 and Japanese men. 13 Testosterone levels can differ among different ethnic groups; Pakistani men have lower testosterone levels than men from Europe, Africa, and the Caribbean.…”
supporting
confidence: 75%
“…Within Uganda, however, testosterone levels showed small, nonsignificant variations compared to population variations seen elsewhere. 11,16 Further investigations into genetic or dietary factors are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related declines in testosterone have been well established in western samples based on both cross-sectional and longitudinal designs (Gray et al, 1991;Feldman et al, 2002;Harman et al, 2001;Morley et al, 1997;Vermuelen et al, 1999). Cross-sectional data reveal age-related declines in men from Zimbabwe (Lukas et al, 2004) and rural Kenya (Campbell et al, 2003), although population variation in this age-related testosterone decline has been observed (Ellison et al, 2002). Although the raging HIV epidemic has heavily impacted sub-Saharan Africa (Piot et al, 2001) and North American data have indicated a high prevalence of low testosterone levels among HIV positive males, particularly those experiencing muscle wasting (Coodley et al, 1994;Dobs, 2003;Salehian et al, 1999), we are not aware of any such data on sub-Saharan African populations.…”
mentioning
confidence: 81%
“…An urban population in Harare, Zimbabwe is intermediate in nutrition and activity between settled Kenyan populations and Western populations (34,50). The Zimbabwe men are mildly underweight, with average body fat at 14.8%, but are not under severe nutritional stress.…”
Section: Discussionmentioning
confidence: 99%